(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Non-motor symptoms (NMS) are common in Parkinson’s disease (PD), affecting almost all patients during their illness. They may appear in early pre-symptomatic stage as well as throughout the disease course. This observational cross sectional study was carried out in the Movement Disorder Clinic, Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka to see the presence of non-motor symptoms in Parkinson’s disease. Seventy-six Parkinson’s Disease patients were recruited during October 2019 to September 2020. Presence of non–motor symptoms (NMSs) was sought by the 30-item Parkinson’s Disease Questionnaire (PDQ-30). All patients (100%) of this study were suffering from one or more non-motor symptoms. Most common non-motor symptoms of Parkinson’s disease were anxiety (78%), fatigue (78%), difficulty in falling or staying sleep (75%), depression (72%), forgetfulness 72%, dizziness (68%), loss of interest in doing activities (66%), flat mood (62%), lack of pleasure (60%), restless leg (59%) & problem in sustaining concentration (50%). Other non-motor symptoms were present in less than 50% patients. Non-motor symptoms are common and often unrecognized in Parkinson`s Disease. Address- ing this issue will help to manage these symptoms and thereby improve quality of life of patients with Parkinson`s Disease. BSMMU J 2021; 14(4): 121-124